2010
DOI: 10.1016/j.jpba.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in the advanced analysis of bioactive fatty acids

Abstract: The consumption of dietary fats have been long associated to chronic diseases such as obesity, diabetes, cancer, arthritis, asthma, and cardiovascular disease; although some controversy still exists in the role of dietary fats in human health, certain fats have demonstrated their positive effect in the modulation of abnormal fatty acid and eicosanoid metabolism, both of them associated to chronic diseases. Among the different fats, some fatty acids can be used as functional ingredients such as alpha-linolenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(70 citation statements)
references
References 301 publications
(284 reference statements)
0
67
0
3
Order By: Relevance
“…However, biochemical analysis proved that D5 (O. ovata 1) strain showed the highest anticancer activity among the cultured dinoflagellats strains and was successfully cultured in f/2 media. Previous studies reported that cultured dinoflagelates are prolific sources for lipid or fatty acid isolation (Rodriguez et al, 2010a). The screening results of our studies emphasized that available lipids including stanols, steroids and polyunsaturated fatty acids are potential metabolites for anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 54%
“…However, biochemical analysis proved that D5 (O. ovata 1) strain showed the highest anticancer activity among the cultured dinoflagellats strains and was successfully cultured in f/2 media. Previous studies reported that cultured dinoflagelates are prolific sources for lipid or fatty acid isolation (Rodriguez et al, 2010a). The screening results of our studies emphasized that available lipids including stanols, steroids and polyunsaturated fatty acids are potential metabolites for anti-inflammatory effects.…”
Section: Discussionmentioning
confidence: 54%
“…Similar approach has been applied for the advanced analysis of food anthocyanins, isoflavones, and flavanols [99], flavonoids [100], phenolic compounds [101,102], carotenoids [103,104], and other phytochemicals in foods [105]. Many times these studies focus on the biological properties of other compounds, as fatty acids [106] or glucosinolates [107] that can have other sources different than plants. The analysis of nutraceuticals is a key issue for which advanced analytical techniques will play a key role [108] as well as for global research in nutrition and dietetics [109].…”
Section: Food Analysis: Current State Of the Art Methodologies And mentioning
confidence: 99%
“…Thus, the selection of GLC parameters such as the temperature program is analytically very important and it mainly depends on the complexity of the FAs present in the sample and the purpose of the analysis. These issues must be known by the analyst, and good reviews on these topics are available in the literature (Seppäenen-Laakso et al, 2002;Kramer et al, 2004;Ratnayake et al, 2006;Destaillats et al, 2007;Rozema et al, 2008;Mossoba and Kramer, 2009;Ruiz-Rodriguez et al, 2010). There are also several standardized methods such as: AOAC Fat in foods 966.06 (2005), AOCS Official Method Ce 1h-05 (2005), AOCS Official Method Ce 1j-07 (2007), AOCS Official Method Ce 2b-11 (2011) and AOCS Official Method Ce 2c-11 (2011).…”
Section: Introductionmentioning
confidence: 99%